2017
DOI: 10.1016/j.fertnstert.2017.02.114
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of female obesity and interaction with race on reproductive potential

Abstract: Across the reproductive spectrum, obesity is associated with greater risks for adverse health outcomes, including higher rates of infertility, subfertility, early pregnancy loss, fetal deaths and stillbirths, congenital anomalies, and pregnancy complications. The excess reproductive morbidity associated with obesity may increase with longer duration, making the current trends among children and young adults particularly critical in terms of their future reproductive potential. Obese women have a lower chance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 121 publications
(100 reference statements)
2
35
1
1
Order By: Relevance
“…In accordance with the literature, 27 31 the risk of having no and only one child showed strong effects in overweight and obese women (BMI ≥25) in stratified analyses ( table 3 ). Nevertheless, the higher risk of having only one child remained in normal-weight women (BMI<25) with the lowest HDL quintile and the highest TG and TG:HDL-c ratio quintiles.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with the literature, 27 31 the risk of having no and only one child showed strong effects in overweight and obese women (BMI ≥25) in stratified analyses ( table 3 ). Nevertheless, the higher risk of having only one child remained in normal-weight women (BMI<25) with the lowest HDL quintile and the highest TG and TG:HDL-c ratio quintiles.…”
Section: Discussionsupporting
confidence: 90%
“…The impact of obesity on in vitro fertilization (IVF) outcomes is controversial, but most studies have shown lower implantation, clinical pregnancy and birth respective rates, and a higher miscarriage rate. Fewer oocytes are collected and fertilized, cycles are longer and require higher amounts of gonadotropins (4,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In a sense, every routine or annual visit can be considered a pre-conception visit. While it is well known that obesity is associated with the risk of anovulation and infertility (Luke, 2017), e.g., polycystic ovarian syndrome, in general, obese women have similar fecundity to those of normal BMI and are also as sexually active. There is, therefore, value in using each visit to help women achieve a healthier weight before becoming pregnant.…”
Section: Pre-gravid Obesitymentioning
confidence: 99%